LEGAL AND ETHICAL PERSPECTIVES ON (BIG) DATA, PLATFORMS, AI AND ALGORITHMS - Ess, Charles; franzke, aline shakti; Kwok, Chi; Chan, Ngai Keung; Bay, Morten; Burk, Dan (AoIR Selected Papers of Internet Research, 2020)
AoIR and the Journal of Information, Communication and Ethics in Society (JICES) share common interests in critical reflection on the ethical and social dimensions of the internet and internet-facilitated communication, and have begun a collaboration aimed at collecting ethically-focused AoIR conference submissions for presentation and critique at AoIR, with a view towards subsequent publication in a special issue of JICES. This panel collects four papers exploring especially the legal and ethical dimensions of new technologies, including data collection and storage as public goods vis-à-vis central questions of justice (Paper 1, Towards a Political Theory of Data Justice: A Public Good Perspective); critiques from Western and non-Western positions of the utilitarianism otherwise driving the platforms’ business models and rationales (Paper 2, Google and Facebook VS Rawls and Lao-Tsu: How Silicon Valley’s utilitarianism and Confucianism are bad for Internet ethics); basic tensions between the rule of law vis-à-vis algorithmic “decision-making” processes in jurisprudence and “surveillance capitalism” (Paper 3, The Jurisprudence of Datafied Law); and a taxonomy of the ethics of AI, algorithms and big data based on an analysis of 90 guidelines from 2017-2020 (Paper 4, A systematic literature Review of ethical Code of Conducts in the field of Internet Research). These papers directly take up the central interests shared between AoIR and JICES in the ethical and social dimensions of the internet and internet-facilitated communication. They offer new insight on legal and ethical aspects of contemporary technologies, some of which will have specific implications for internet research ethics.